Studying Community Librarianship through Historical Writings on Public Library Programming Activities: American, British, and Anglo-Scandinavian Perspectives - Mathiasson, Mia Høj (Library trends, 2024)
This paper offers a historical perspective on community librarianship, diving into historical writings on programs and programming activities in a public library context since the 1920s from an American, a British, and a Scandinavian perspective. The paper aims to inform the understanding of programs and programming activities, identifying the underlying objectives and ideologies that have shaped this central part of community librarianship. By employing a synoptic approach to the study of these texts, the paper bridges terminological and conceptual differences, encompassing the educational, cultural, social, and informational aspects of public library programming. Based on the literature studied, four main objectives are identified: inspirational, educational, recreational, and relational. Moreover, the paper highlights how librarians have played a central role in driving the development of these services, stressing the importance of the interests and motivation of individuals. Reflecting on how such activities have been subjects of value-based discussions within the library professional field for over a century, this paper offers new insights into community librarianship. As such, it constitutes foundational work for future research and discussions within this field of study.